Carbon nanotubes grown on carbon fiber yarns by a low temperature CVD method: A significant enhancement of the interfacial adhesion between carbon fiber/epoxy matrix hierarchical composites. (March 2017) - Felisberto, Marcos; Tzounis, Lazaros; Sacco, Leandro; Stamm, Manfred; Candal, Roberto; Rubiolo, Gerardo H.; Goyanes, Silvia
Abstract: In this work, we show that the interfacial adhesion between carbon fibers (CFs) and epoxy matrix in laminated composites can be significantly enhanced by the chemical vapor deposition (CVD) growth of multiwalled carbon nanotubes (MWCNTs) onto the fiber surfaces at low temperatures. The key process parameter was the deposition of catalytic nickel nanoparticles (NPs) onto the CFs at room temperature by a low energy double target DC sputtering system. This protocol enabled the growth of CNTs without any detrimental effect on the fiber properties, and enhanced effectively the adhesion between fibers and matrix. Fractographic investigations of single fiber/epoxy composites demonstrated an improved interfacial adhesion between the 'hierarchical' fibers (CF-CNT) with the epoxy matrix as compared to the bare carbon fibers. The developed protocol is versatile and it is envisioned to be easily scaled-up for volume production of CF-CNT, giving rise to high mechanical performance structural composites. Highlights: Upscalable method for the growth of MWCNTs onto carbon fibers at low temperatures. Entirely covered carbon fibers with carbon nanotubes. Synthesis methodology do not degrade the mechanical properties of the carbon fibers. Catalyst nickel nanoparticles deposited by sputtering at room temperature. Increases on the interfacial adhesion carbon fibers/epoxy matrix.